Studies on Schismatoglottideae (Araceae) of Borneo XXXXI: Additional new species of Bucephalandra - Wong, Sin Yeng; Boyce, P.C (BGBM Berlin-Dahlem., 2014)
Two new species of Bucephalandra Schott are described and illustrated from Kalimantan Barat, Indonesian Borneo: B. micrantha S. Y. Wong & P. C. Boyce and B. spathulifolia Engl. ex S. Y. Wong & P. C. Boyce, the epithet of the second name adopted from an unpublished Engler name: “Microcasia spathulifolia”. Together these take Bucephalandra to 29 species. Both novelties are illustrated from living plants, and inserted into the most recent identification key to Bucephalandra species.